Model predictive current control of a proposed single-switch three-level active rectifier applied to EV battery chargers - Monteiro, Vitor (2016)
This paper presents a model predictive current control applied to a proposed new topology of single-switch three-level (SSTL) active rectifier, which is exemplified in an application of single-phase battery charger for electric vehicles (EVs). During each sampling period, this current control scheme selects the state of the SSTL active rectifier that minimizes the error between the grid current and its reference. Using this strategy it is possible to obtain sinusoidal grid currents with low total harmonic distortion and unitary power factor, which is one of the main requirements for EVs chargers. The paper presents in detail the principle of operation of the SSTL active rectifier, the digital control algorithm and the EV battery charger (where is incorporated the SSTL active rectifier) that was used in the experimental verification. The obtained experimental results confirm the correct application of the model predictive current control applied to the proposed SSTL active rectifier.